2000
DOI: 10.1177/002215540004800502
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Subcellular Localization of Catalase in the Heart of Transgenic Mice

Abstract: Previous studies have described a cardiac-specific, catalase-overexpressing transgenic mouse model that was used to study myocardial oxidative injury. This study was undertaken to demonstrate cellular and subcellular localization of catalase in the hearts of transgenic mice. By the light microscopic immunoperoxidase method, we found that the overexpressed catalase was exclusively localized in cardiomyocytes. The ratios of immunoreactive cardiomyocytes in the heart were quite different among three transgenic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 27 publications
(34 reference statements)
4
51
1
1
Order By: Relevance
“…Our findings are parallel to the findings of Bingöl and Kocamış [17] , Morikawa et al [29] , Zhou and Kang [30] regarding presence of immunoreactivity in the cortex of the kidney, especially in proximal tubuli in the inner cortex portion and absence of reaction in distal tubuli, vascular endothelium and connective tissue. Kidney and especially proximal KORAL TAŞÇI, DEPREM, BİNGÖL ELİŞ YILDIZ, ASLAN [15] .…”
Section: Ergin and Başaloğlusupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings are parallel to the findings of Bingöl and Kocamış [17] , Morikawa et al [29] , Zhou and Kang [30] regarding presence of immunoreactivity in the cortex of the kidney, especially in proximal tubuli in the inner cortex portion and absence of reaction in distal tubuli, vascular endothelium and connective tissue. Kidney and especially proximal KORAL TAŞÇI, DEPREM, BİNGÖL ELİŞ YILDIZ, ASLAN [15] .…”
Section: Ergin and Başaloğlusupporting
confidence: 91%
“…Similarly in their study, Morikawa et al [29] studied immunohistochemical localization of catalase in tissues of mammals and they reported that the reaction is in the cytoplasm of proximal tubuli cells of the kidney and that no specific reaction is present in distal tubule epithelium, connective tissue and blood vessels. Zhou and Kang [30] studied immunohistochemical localization of catalase in various tissues in transgenic mice and stated that there is cytoplasmic reaction in proximal tubuli of kidney. They have observed that this present reaction in proximal tubuli is weaker in the outer part of the cortex, stronger in the inner part and not present in distal tubuli, glomeruli, loop of Henle, collector tubes and medulla [30] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, protection with PostC and AB prevents the reduction of the levels of the cytosolic Cu/Zn-SOD, which are otherwise reduced after I/R. The dichotomy on activities and levels between cytosolic and organelle confined enzymes [68], supports a role for compartmentalization of redox-environment in late reperfusion [52].…”
Section: Late Reperfusionmentioning
confidence: 99%
“…Indeed, we have recently demonstrated that Sirt1 prevents apoptosis through the induction of catalase in HK-2 cells (7). Catalase is located in peroxisome fraction, which has been shown to promote peroxisome proliferation (26); the supplementation of peroxisome activator nafenopin results in a sustained increase in the number of peroxisomes with concomitant increases in catalase activity (27). Increased catalase therefore may eliminate H 2 O 2 within peroxisome, which possibly leads to the mitigation of the damages to peroxisome.…”
Section: Discussionmentioning
confidence: 99%